Analisa dan Perancangan Sistem E-Voting Pemilu Raya BEM di Universitas Ichsan Gorontalo: Analisa dan Perancangan Sistem E-Voting Pemilu Raya BEM di Universitas Ichsan Gorontalo - sulistiawati Rahayu Ahmad; Siti Andini Utiarahman; Jorry Karim (JSAI (Journal Scientific and Applied Informatics), 2022)
The Student Executive Board (BEM) is among the organizations in universities formed by students. Through BEM, students can learn to socialize, politics and democracy. Every year Ichsan University conducts BEM ELECTION activities to elect BEM Presidential Candidates. In the process, there is a problem where the BEM ELECTIONS have decreased student political participation because students have to come to campus, and the process of recapitulation of vote counting is quite long. The purpose of the study was to design a web-based e-voting application that all active students can use to participate in the UNISAN BEM ELECTION without having to come directly to campus. The process and results of the UNISAN BEM ELECTIONS were fast, effective and transparent. Data collection techniques carried out observations, interviews and literature studies with system development using the waterfall method. The system design is in the form of a UML diagram. Creation with PHP and MySQL languages for databases. The test results resulted in cyclomatic complexity. In the calculation of cyclomatic complexity, if V(G) = E-N+2, the result is equal to V(G) = P+1. The results of the UNISAN BEM ELECTION research were fast, effective and transparent.